2016
DOI: 10.1002/anie.201604679
|View full text |Cite
|
Sign up to set email alerts
|

[5+2] Cycloaddition of 2‐(2‐Aminoethyl)oxiranes with Alkynes via Epoxide Ring‐Opening: A Facile Access to Azepines

Abstract: A new FeCl3 and BF3 ⋅OEt2 co-catalyzed tandem hetero-[5+2] cycloaddition of 2-(2-aminoethyl)oxiranes with a wide range of alkynes, including terminal alkynes and alkyl-substituted internal alkynes is presented. This is the first example of rapid and facile production of diverse 2,3-dihydro-1H-azepines through a sequence of epoxide ring-opening, annulation, and dehydroxylation with broad substrate scope and exquisite selectivity control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 87 publications
0
9
0
1
Order By: Relevance
“…After a series of trials, we established a Lewis acid promoted hetero-[5+2]-cycloaddition reaction of 2-(2-aminoethyl)oxiranes with alkynes for the synthesis of 2,3-dihydro-1H-azepines (Scheme 7). 8 Using FeCl 3 and BF 3 •OEt 2 as cocatalysts, this rapid and facile reaction produced diverse 2,3-dihydro-1H-azepines through a sequence of epoxide ring-opening, annulation, and dehydroxylation with broad substrate scope and exquisite selectivity control.…”
Section: Scheme 6 Possible Mechanisms Of Agsbf 6 -Catalyzed [5+2] Cycmentioning
confidence: 99%
“…After a series of trials, we established a Lewis acid promoted hetero-[5+2]-cycloaddition reaction of 2-(2-aminoethyl)oxiranes with alkynes for the synthesis of 2,3-dihydro-1H-azepines (Scheme 7). 8 Using FeCl 3 and BF 3 •OEt 2 as cocatalysts, this rapid and facile reaction produced diverse 2,3-dihydro-1H-azepines through a sequence of epoxide ring-opening, annulation, and dehydroxylation with broad substrate scope and exquisite selectivity control.…”
Section: Scheme 6 Possible Mechanisms Of Agsbf 6 -Catalyzed [5+2] Cycmentioning
confidence: 99%
“…to build molecular complexity.A lthough various cycloaddition reactions have been developed for the synthesis of complex four-, five-, and six-membered rings with excellent control of regio-and stereoselectivity,far fewer methods are available for the formation of highly substituted sevenmembered rings. [1][2][3] Since the first report by Hendrickson in 1980, [4] oxidopyrylium ylide based [5+ +2] cycloaddition [5] has emerged as apowerful transformation for the construction of seven-membered carbocycles. [2,6,7] Most previous studies have focused on intramolecular oxidopyrylium-alkene cycloaddition with the alkene 2p components tethered to C2 or C6 position, that is,type Ioxidopyrylium-alkene cycloaddition.…”
Section: Cycloadditionisoneofthemostefficientandpowerfulwaysmentioning
confidence: 99%
“…
We have developed the first intermolecular hetero-[5+ +2] cycloaddition reaction between oxidopyrylium ylides and cyclic imines with excellent control of regio-and stereoselectivity.S urprisingly,d ivergent stereochemistry was observed depending on the substitution pattern of the oxidopyrylium ylide.T his new reaction provides quicka ccess to highly substituted nitrogen-containing seven-membered rings-azepanes.N otably,abroad range of oxidopyrylium ylides and cyclic imines participate in this novel hetero-[5+ +2] cycloaddition reaction and the cycloadducts can be readily transformed into the core skeletons of bioactive natural products.D FT calculations revealed that the cycloaddition proceeds through as tepwise pathway and the imine nitrogen atom serves as the nucleophile to initiate the cycloaddition.
Cycloadditionisoneofthemostefficientandpowerfulwaysto build molecular complexity.A lthough various cycloaddition reactions have been developed for the synthesis of complex four-, five-, and six-membered rings with excellent control of regio-and stereoselectivity,far fewer methods are available for the formation of highly substituted sevenmembered rings. [1][2][3] Since the first report by Hendrickson in 1980, [4] oxidopyrylium ylide based [5+ +2] cycloaddition [5] has emerged as apowerful transformation for the construction of seven-membered carbocycles. [2,6,7] Most previous studies have focused on intramolecular oxidopyrylium-alkene cycloaddition with the alkene 2p components tethered to C2 or C6 position, that is,type Ioxidopyrylium-alkene cycloaddition.
…”
mentioning
confidence: 99%
“…[9] However, most of the reported methods require multiple-step synthesis. Besides, Lewis acidcatalyzed intramolecular or intermolecular cycloaddition [10] and Et 3 N-catalyzed tandem formal [4 + 3] annulation/decarboxylation/isomerization of methyl coumalates with imine esters [11] have also proven to be alternative routes for the construction of azepine derivatives, but the starting materials require multi-step preparation. Recently, transition-metal-catalyzed intramolecular or intermolecular cyclization reactions have provided a powerful and useful alternative strategy for the construction of azepine derivatives with various catalysts such as Rh, [12] Ir, [13] Ru, [14] Pd, [15] Ag [16] and Hf.…”
Section: Introductionmentioning
confidence: 99%